Turnieje oksfordzkie jako narzędzie rozwijające publiczną debatę = Oxford-style debates as a tool for developing public discourse - Dworska, Żaklina; Lekhchine, Omar; Pankiewicz, Jakub; Bajon, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Oxford-style debate, tracing its roots back to the 19th century, constitutes a significant tool in shaping communication skills, fostering political thinking, and influencing public discourse. Participation in debate tournaments helps develop analytical skills, critical thinking, effective argumentation, and rhetoric. It supports the cultivation of public speaking abilities and the learning of compromise.
Keywords: debata oksfordzka; myśl polityczna; dyskurs publiczny; wystąpienia publiczne; komunikacja; Oxford-style debate; political thought; public discourse; public speaking; communication